Screening and genome analysis of heat-resistant and antioxidant lactic acid bacteria from Holstein cow milk - Wang, Jiali; Liu, Yunjiang; Zheng, Haohong; Xin, Jialiang; Zhong, Zhijun; Liu, Haifeng; Huang, Yixin; Fu, Hualin; Zhou, Ziyao; Peng, Guangneng (Frontiers in Microbiology, 2024)
BackgroundHeat stress significantly impacts dairy cows, primarily through oxidative stress, which undermines their health. The problem is exacerbated by the ongoing global warming trend. Lactic acid bacteria (LAB) are safe, economical, and readily accessible options for enhancing the host’s antioxidant defenses and preventing oxidative damage. They have been proven effective in alleviating heat stress-related damage, making them an excellent choice for protecting dairy cows from the adverse effects of heat stress.MethodIn this study, five strains of LAB from Holstein cow milk (Lactobacillus plantarum L5, L14, L17, L19, L20) were evaluated for their heat resistance and antioxidant capacity by evaluating the growth characteristics and tolerance of the strains under high-temperature conditions, as well as their H2O2 tolerance, free radical scavenging ability (DPPH, OH−, ABTS), reducing ability, and EPS production ability. Furthermore, we employed Caco-2 cells to assess the adhesion rate of the strain, thereby confirming its ability to successfully colonize the host’s intestinal tract and ensuring the effective execution of its probiotic functions. The strain with excellent heat resistance and antioxidant capacity was then subjected to genomic analysis to gain insight into the molecular mechanisms behind their heat resistance, antioxidant capacity, and safety.ResultsAmong the two strains, Lactobacillus plantarum L19 emerges as a highly promising candidate. The strain exhibits robust growth even at high temperatures at 40°C and maintains a survival rate of 16.42% at the extreme temperature of 65°C. Furthermore, it demonstrates superior tolerance to hydrogen peroxide (27.3%), and possesses a notably higher free radical scavenging capacity with a high adhesion rate to Caco-2 cell (22.19%) compared to the other four strains tested. Genomic analysis revealed its’ genome has 17 genes related to antioxidants and three genes related to heat resistance. Importantly, L19 lacks any resistance genes, ensuring its safety as a probiotic.ConclusionThe results imply that Lactobacillus plantarum L19 has the potential to serve as an effective food additive in mitigating damages associated with heat stress. This research offers a valuable reference for the prevention and management of heat stress in dairy cows, while also expanding the scope of applications for LAB derived from cow milk.